2016
DOI: 10.1371/journal.pone.0147854
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Nutritional Status of Overseas Refugee Children with Low Income Children in Washington State

Abstract: IntroductionThe extent that the dual burden of undernutrition and overnutrition affects refugee children before resettlement in the US is not well described.ObjectiveTo describe the prevalence of wasting, stunting, overweight, and obesity among refugee children ages 0–10 years at their overseas medical screening examination prior to resettlement in Washington State (WA), and to compare the nutritional status of refugee children with that of low-income children in WA.MethodsWe analyzed anthropometric measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 15 publications
3
32
0
Order By: Relevance
“…US researchers report similar findings, with Burmese children having the highest prevalence of stunting compared to African (specifically Somali) and Middle Eastern (mainly Iraqi) children . The authors speculate that the higher prevalence of stunting among Burmese children may be due to more prolonged periods of suboptimal nutrition and illness …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…US researchers report similar findings, with Burmese children having the highest prevalence of stunting compared to African (specifically Somali) and Middle Eastern (mainly Iraqi) children . The authors speculate that the higher prevalence of stunting among Burmese children may be due to more prolonged periods of suboptimal nutrition and illness …”
Section: Discussionsupporting
confidence: 77%
“…The prevalence rate of 11.8% of underweight children 24 months at time of referral differs from US data where 17.3% of paediatric refugees were underweight just prior to resettlement . Anecdotally, lower WA rates may reflect resettlement bias away from severe malnutrition.…”
Section: Discussionsupporting
confidence: 76%
“…Malnutrition is also a common pre-migration experience of refugee adults and children. A recent study of 982 refugee children aged 0 to 10 newly arrived in the United States found that 45% experienced at least one form of malnutrition (Dawson-Hahn, Pak-Gorstein, Hoopes, & Matheson, 2016).…”
Section: Pre-migration and Transitionmentioning
confidence: 99%
“…14 -16 Refugee children arrive in the United States with variable nutritional status based on their preresettlement experiences. 9,12,17,18 Although several studies have reported an increase in the prevalence of obesity and obesity-related diseases among adult refugees and an increase in their BMI trajectories after US resettlement, the data among child refugees is limited. 19,20 Two small studies demonstrated a trend toward increasing obesity prevalence among refugee children.…”
Section: What This Study Addsmentioning
confidence: 99%